2020
DOI: 10.1111/bpa.12878
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for integrative multi‐omic approaches to explore Alzheimer's disease mechanisms

Abstract: The past decade has seen the maturation of multiple different forms of high‐dimensional molecular profiling to the point that these methods could be deployed in initially hundreds and more recently thousands of human samples. In the field of Alzheimer's disease (AD), these profiles have been applied to the target organ: the aging brain. In a growing number of cases, the same samples were profiled with multiple different approaches, yielding genetic, transcriptomic, epigenomic and proteomic data. Here, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Molecular profiling and integrative multi‐omics approaches are the current focus in LOAD genetic research toward the identification the molecular drivers of LOAD. 47 , 48 , 49 , 50 Several bioinformatics approaches have been described to study the functional role of GWAS‐enhancer elements and variants on gene expression and in turn, development or progression of neurodegenerative diseases including LOAD. These approaches have included fine mapping DNA methylation sites in prefrontal cortex neurons from brains with different degrees of Alzheimer's disease pathology, 51 cataloguing enhancers in LOAD regions and mapping promoter‐enhancer interaction using Circular Chromosomal Conformation Capture (4C) data to prioritize genes for experimental follow‐up, 28 and integrating datasets of enhancer activity, TF binding sites, and eQTL 10 , 52 , 53 to characterize the effects of non‐coding genetic variation associated with LOAD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling and integrative multi‐omics approaches are the current focus in LOAD genetic research toward the identification the molecular drivers of LOAD. 47 , 48 , 49 , 50 Several bioinformatics approaches have been described to study the functional role of GWAS‐enhancer elements and variants on gene expression and in turn, development or progression of neurodegenerative diseases including LOAD. These approaches have included fine mapping DNA methylation sites in prefrontal cortex neurons from brains with different degrees of Alzheimer's disease pathology, 51 cataloguing enhancers in LOAD regions and mapping promoter‐enhancer interaction using Circular Chromosomal Conformation Capture (4C) data to prioritize genes for experimental follow‐up, 28 and integrating datasets of enhancer activity, TF binding sites, and eQTL 10 , 52 , 53 to characterize the effects of non‐coding genetic variation associated with LOAD risk.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of powerful computational frameworks now offers multilayer inter‐regulatory approaches to understand the development and course of AD, while accounting for inter‐individual differences in genotype and exposure to environmental risk factors. As such, multi‐omics approaches––that include an integrative analysis of various layers of epigenetic regulation––and associated data science tools show great promise in the development of novel diagnostic tools and treatment strategies for AD, with further details on this approach provided elsewhere in this mini‐symposium [36].…”
Section: Multi‐omics Approachesmentioning
confidence: 99%
“…Importantly, it has been shown that several multi-'omic data types, including histone acetylation [15], metabolomics [16][17][18][19][20] and proteomics [21], are not only associated with AD neuropathologies, but also contributed information to associations that is missed with RNAseq alone [8,21]. As such, integrating data modalities into subtyping pipelines has been an active area of research [22,23], and large-scale cohort studies of aging that include brain donation and multi-'omic characterization, such as those from the Accelerating Medicines Partnership for Alzheimer's Disease (AMP-AD) consortium, now offer opportunities for developing highly integrative models of cognitive decline [24]. Methods development in high-dimensional feature integration have also facilitated these analyses [25,26] , though not yet in pathological aging or AD.…”
Section: Introductionmentioning
confidence: 99%